Re‐evaluation of alginic acid and its sodium, potassium, ammonium and calcium salts (E 400–E 404) as food additives. (10th November 2017) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; Lambré, Claude; et al.
Abstract: The present opinion deals with the re‐evaluation of alginic acid and its sodium, potassium, ammonium and calcium salts (E 400–E 404) when used as food additives. Alginic acid and its salts (E 400–E 404) are authorised food additives in the EU in accordance with Annex II and Annex III to Regulation (EC) No 1333/2008. Following the conceptual framework for the risk assessment of certain food additives re‐evaluated under Commission Regulation (EU) No 257/2010, the Panel concluded that there was no need for a numerical Acceptable Daily Intake (ADI) for alginic acid and its salts (E 400, E 401, E 402, E 403 and E 404), and that there was no safety concern at the level of the refined exposure assessment for the reported uses of alginic acid and its salts (E 400, E 401, E 402, E 403 and E 404) as food additives. The Panel further concluded that exposure of infants and young children to alginic acid and its salts (E 400, E 401, E 402, E 403 and E 404) by the use of these food additives should stay below therapeutic dosages for these population groups at which side‐effects could occur. Concerning the use of alginic acid and its salts (E 400, E 401, E 402, E 403 and E 404) in 'dietary foods for special medical purposes and special formulae for infants' (Food category 13.1.5.1) and 'in dietary foods for babies and young children for special medical purposes as defined in Directive 1999/21/EC' (Food category 13.1.5.2), the Panel further concluded that the available data did not allow an adequate assessment of the safety of alginic acid and its salts (E 400, E 401, E 402, E 403 and E 404) in infants and young children consuming the food belonging to the categories 13.1.5.1 and 13.1.5.2.